Wasiat Yang Ideal Dalam Ruang Lingkup Hukum Pembuktian di Indonesia - Sari, Defita Permata (Faculty of Law Universitas Islam Indonesia, 2024)
Regarding wills, there are fundamental differences between the Civil Code and the Compilation of Islamic Law. The difference is in the will made without a Notary deed or orally which is recognized in KHI, but not recognized in the Civil Code because it is not written and not made before a Notary. Whereas the issue of wills in inheritance is very vulnerable to disputes between heirs, where later the evidentiary power of the will is very decisive for the settlement of disputes that occur. Dispute resolution is closely related to evidence. The difference makes many parties, especially heirs, a dilemma to follow the provisions of KHI or the Civil Code. Therefore, it is necessary to study the ideality of the will form in evidentiary law. This is important, because it is not uncommon for inheritance issues to become objects of dispute. Therefore, the researcher formulates a problem formulation regarding